O sigma sob suspeita: a polícia política e a repressão ao integralismo no Espírito Santo (1933-1942) - Stanger, Diego (2014)
This paper examines a portion of the Political History of the Espírito Santo, set mainly in the period of the government of João Punaro Bley, who was in command of the state between the years 1930-1943, but our time frame is established between the years from 1933 to 1942. Temporal delimitation was set based on medullary documentary corpus of our research, the files of the Police Policy, better known as Delegacia de Ordem Política e Social (DOPS). This documentation deals specifically with the Ação Integralista Brasileira in the Espírito Santo, and part was produced by the police institution itself and the other was seized when the official repression began to move. The choice of the starting date, the year 1933 was due to the fact that the same have been the foundation of the first nucleus of Ação Integralista Brasileira state of Espírito Santo, while the final milestone , the year 1942, when the government was Brazil declared war on the member countries of the Axis (Germany, Italy and Japan), which led to new crackdown on former members of Integralista movement, and consequent production of a series of charts that identify former members of AIB in the state. The repression of Integralism in 1942 was justified because the character of the movement, inspired by the principles of European fascism, which was the basis of the regimes of the Axis nations. But before the AIB gain the status of an enemy of the government of Getúlio Vargas, which happened in 1938 , following unsuccessful coup against the political leader said, they had during the 1930s, large figure on the political scene national as well as on site. In addition, AIB was allied regime, especially in the fight against communism. The dissertation seeks to analyze the construction of an anti - fundamentalist discourse, through the documents seized and produced by Precinct Political and Social Order. As well as building a panorama on the organization and performance of Brazilian Ação Integralista in the Espírito Santo